Segmentação automática de imagens doppler transversais modo-b da bifurcação carotídea / Automatic segmentation in transverse ultrasound bmode images of the carotid artery - Catarina Castro (2018)
Ultrasound imaging is extremely important for the assessment of disease severity in the carotid arteries. The high complexity of irregular structures in transverse ultrasound images of abnormal bifurcation of the common carotid artery brings tremendous difficulty to segmentation and identification of vulnerable atherosclerotic plaques. Automatic algorithms for image segmentation provide results minimizing the variability caused by subjective decisions and different operators. The proposed algorithm for automatic segmentation of B-mode transverse images of the carotid bifurcation facilitates structure selection for further analyses and provides an evaluation performance of the methodology and a means for comparing different algorithm settings. Patient-specific Doppler imaging is used to illustrate the new developed methodology.